Cervical Flexor–Extensor Muscle Disparity in Monomelic Amyotrophy (Hirayama Disease): Evidence from a Comprehensive Morphometric Evaluation of Subaxial Paraspinal Musculature - Thakar, Sumit; Rajagopal, Niranjana; Alle, Prashanth; Aryan, Saritha; Hegde, Alangar (Asian Journal of Neurosurgery, 2022)
Background Monomelic amyotrophy (Hirayama disease) has been established to have accompanied biomechanical abnormalities such as flexion hypermobility and sagittal imbalance. Paraspinal muscles, the major contributor to cervical biomechanics, have, however, not been comprehensively evaluated in the disease. The objective of this study was to compare the morphology of the subaxial cervical paraspinal musculature in patients with and without Hirayama disease.Materials and Methods A retrospective case-control study of 64 patients with Hirayama disease and 64 age- and sex-matched controls was performed. Cross-sectional areas (CSAs) of the superficial and deep flexors and extensors from C3 to C7 were measured on T2-weighted magnetic resonance imaging sequences. Student's t-test was used to compare differences between the paraspinal muscle CSAs in the study and control groups.Results Compared with controls, patients with Hirayama disease were found to have larger flexors and smaller extensors at all levels. The overall subaxial muscle area values for superficial flexors and deep flexors were significantly larger (p < 0.0001) in patients, while the corresponding superficial extensor and deep extensor area values were significantly smaller than in controls (p = 0.01 and < 0.0001, respectively). The patient group demonstrated stronger subaxial deep flexor–deep extensor, superficial flexor–superficial extensor, and total flexor–total extensor ratios (p < 0.0001).Conclusion Patients with Hirayama disease have morphometric alterations at all levels of their subaxial cervical paraspinal musculature. These patients have abnormally large flexors and small extensors compared with controls. This flexor–extensor muscle disparity could be utilized as a potentially modifiable factor in the management of the disease.
Keywords: Hirayama disease; paraspinal muscles; morphometric; flexor–extensor disparity